Health impacts of public pawnshops in Industrialising Tokyo - Tatsuki Inoue (Asia‐Pacific Economic History Review, 2026)
Abstract This study examines whether expanded credit access through low‐interest small loans relaxed liquidity constraints among poor households and improved early‐life health in industrialising Tokyo. Using ward‐level panel data for 1927–1935, this study shows that public pawnshop lending was associated with 4% and 5% reductions in infant and foetal death rates, respectively. Historical evidence suggests channels through improved hygiene, protection against cold exposure, safer pregnancy and childbirth, and short‐term nutritional support. A cost‐effectiveness calculation indicates that public pawnshops were an efficient public investment. Private for‐profit pawnshops, despite larger operations, showed no significant association with health improvements.